Move to nocturnality not a universal trend in carnivore species on disturbed landscapes. Issue 8 (18th June 2020) - Frey, Sandra; Volpe, J. P.; Heim, N. A.; Paczkowski, J.; Fisher, J. T.
Abstract : Anthropogenic landscape change is a leading driver of biodiversity loss. Preceding dramatic changes such as wildlife population declines and range shifts, more subtle responses may signal impending larger‐scale change. For example, disturbance‐induced shifts to species' activity patterns may disrupt temporal niche partitioning along the 24‐h time axis, compromising community structure via altered competitive interactions. We investigated the impacts of human landscape disturbance on species' activity patterns and temporal niche partitioning in the Canadian Rocky Mountain carnivore guild using camera trap images collected across two regions encompassing a wide gradient of human footprint. Applying kernel density estimation techniques, we tested for carnivore species' activity shifts 1) between a low versus high disturbance landscape, and 2) in relation to site‐scale disturbance. To test our hypothesis that human disturbance impacts species' temporal niche partitioning, we modelled activity overlap between co‐occurring carnivore species in relation to natural and anthropogenic landscape features, as well as carnivore community composition. Multiple carnivore species altered activity patterns between the low versus high disturbance landscapes and camera sites, but these shifts varied considerably among species. While wolves appeared to increase nocturnal activity in relation to disturbance, coyote activity consistently trended towards cathemerality and marten increased diurnal activity. Detecting effects of landscape disturbance on activity overlap between co‐occurring species was highly sensitive to site‐level detection sample sizes, and our results suggest altered temporal niche partitioning between marten and wolverine in relation to forest cover. This study indicates that mesocarnivores may respond differently and perhaps indirectly to anthropogenic disturbance compared to apex predators. Apex predator shifts to nocturnality may facilitate a 'behavioural release' in mesocarnivores. This may be a likely component of mesocarnivore population release, with important management implications for ecological communities on disturbed landscapes.